Observations on pottery finds from the Eastern Mediterranean in Viminacium (Serbia): the Camulodunum 189 amphorae - Raičković Savić, Angelina; Mitić, Ana (Rei Cretariae Romanae Fautorum Acta, 2024)
This paper presents the find of amphorae of the type Camulodunum 189, discovered during recent research activities conducted around the castrum, in Viminacium. New examples of this form of amphorae have supplemented the knowledge of their presence in this part of the empire and indicated considerably more developed trade connections between distant provinces within the empire. Archaeological units in which pieces of amphorae, as well as a whole one, were discovered were dated into the period of the founding of the legionary camp, in the final decades of the 1st and the 2nd century.